Factors that increase the incidence of mortality due to brain vascular accident (Research, Society and Development, 2022)
Stroke is one of the main causes of hospitalizations and mortality, measuring its magnitude as a public health problem. It presents cognitive and neuromuscular changes that can manifest in two ways: ischemic and hemorrhagic. The objective of this work was to identify in the literature the factors that can increase the incidence of stroke mortality in Emergency Units (UE). This is a systematic review study whose descriptors used were: Stroke; Mortality and Emergencies. Complete articles were used that addressed the theme, published in the last ten years in Portuguese and English. Analysis of the articles was obtained through a careful reading of their titles, abstracts and contents. In sequence, the research sample consisted of eleven articles, being cataloged in an adapted document analysis file and organized as follows: journal / year; title; author (s); study objective; method; main results and conclusion. After categorization, a descriptive analysis of the data was performed. The results of this study allowed us to determine that other risk factors are little discussed, but they increase the possibility of stroke mortality. These results point to the need for intervention in several fields: qualification of people, use of strategies and tools that reduce the response time to start assisting stroke victims, as well as training directed to the population, with the objective of early recognition of stroke.